PENERAPAN SISTEM PENDUKUNG KEPUTUSAN METODE FUZZY TSUKAMOTO DALAM PENGOPTIMALAN PRODUKSI BARANG BERDASARKAN DATA PERSEDIAAN DAN JUMLAH PERMINTAAN DI LOVERANDLIARS CLOTH - Zarkasi, Ahmad; Widyastuti, Naniek; Kumalasari, Erna (Jurnal Script, 2015)
ABSTRACTWith the development of science and technology, the use of computer services in all aspects of life already is a necessity, especially in industry. Loverandliars engaged in the production of goods, depending on sales and demand for individual and inter-industry. This thesis discusses the application of fuzzy logic in solving optimization of production amount, in this case using Tsukamoto method and the method of Mamdani and Sugeno method as a comparison. From this method is expected to estimate the amount of production and sales is based on the number of requests that are applied in a decision support system. Enough so that in making decisions with input data required by DSS (Decision Support System), to be processed by the method Tsukamoto to be output (output) in the form of the determination of the amount of goods to be produced. The first step problem solving optimization Tsukamoto products by using the method of determining the variables that are firmly set, the second step is to convert the input into a set of fuzzy variables with fuzzification process, the third step is a data processing method Fuzzy set minimum and maximum. In the process variable input data using an application supporting the Netbeans 8.0 editor. From the analysis of direct comparison with the original data in the calculation of production at the company Loverandliars can be concluded that the method that most closely is the truth value of production obtained by processing the data using the method Tsukamoto.Keywords: DSS, Tsukamoto, Mamdani dan Sugeno, Production, Fuzzy.